2023
DOI: 10.3390/su15076075
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Self-Weight Loading Standing Trees to Determine Its Critical Buckling Height

Abstract: A tree may receive compression and flexure combination, and the structural analysis governed by the building code may be capable of estimating the tree’s safety in the built environment. This study proposed to refer to the building code to check the tree dimension adequacy resisting the load. This study simplified the case by focusing only on the self-weight and ignoring the external loads; therefore, the buckling analysis of a slender tapered round column subjected to compression is advocated. Buckling occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…A tree stem's diameter at the top (D t ) is usually smaller than the diameter at breast height (D bh ). Its three-dimensional shape may resemble a truncated cone [79], sometimes called a conical frustum, as the best-fit idealized standard geometric form. The tree's or log's tapered stem volume equations, empirically proposed by foresters, are Equations ( 30)-( 34) [80].…”
Section: Ellipse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A tree stem's diameter at the top (D t ) is usually smaller than the diameter at breast height (D bh ). Its three-dimensional shape may resemble a truncated cone [79], sometimes called a conical frustum, as the best-fit idealized standard geometric form. The tree's or log's tapered stem volume equations, empirically proposed by foresters, are Equations ( 30)-( 34) [80].…”
Section: Ellipse Modelmentioning
confidence: 99%
“…The resultant of wind, snow, and unsymmetric crown self-weight generate the non-eccentric compressive load the stem receives. Their combination with the bending moment triggers buckling, severely reducing its load-bearing capacity [79,[81][82][83][84][85]. The buckling generates compressive stress in half of the stem and tensile stress in the other half.…”
Section: Ellipse Modelmentioning
confidence: 99%
“…A tree stem may be more similar to truncated cone 3D geometry, a synonym to a conical frustum, than a cylinder [71]; it commonly tappers upward, the bottom diameter is the biggest, and it becomes smaller when nearer to the top. As a product of its evolution, trees commonly have butt swell (bottom thickening), where the stem near the base becomes greatly enlarged to support self-weight loads (i.e., stem and canopy weight) and external loads (i.e., wind and snow mound).…”
Section: Diametermentioning
confidence: 99%
“…The validity of this theory was verified by McMahon, who confirmed that it accurately fits trees of various shapes 2 , 3 . Greenhill's scaling law, with its simplicity and applicability, has been used extensively in forest science and ecology 4 9 .…”
Section: Introductionmentioning
confidence: 99%